Pengaruh Motor Educability Terhadap Kemampuan Teknik Dasar dalam Kegiatan Ekstrakurikuler Futsal Siswi Sekolah Menengah Pertama - Septi Nur Widarto; Ega Trisna Rahayu; Aria Kusuma Yuda (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of motor educability on the basic skills of futsal games for extracurricular participants at SMP N 1 Anjatan. This type of research is an experimental “one group pretest posttest design The population of this study were extracurricular participants at SMP N 1 Anjatan, The sample used is saturated sample. The instrumen used is a futsal skill test from Abdul Narlan (2020: 170-174). Results and conclusions about the effect of motor educability on basic futsal skills. There is a significant effect of motor educability on basic futsal skills. So that by using motor educability as a treatment in futsal basic skills learning activities there is a change or improvement in performing basic futsal technical skills.